Potential Criteria to Determine a Waqf-Based Forest Location: Case Study: Bogor Waqf Forest, Bogor, Indonesia - Jannah, Miftahul; Sarkawi, Azila Ahmad; Othman, Jamilah (Jurnal Manajemen Hutan Tropika, 2024)
Waqf-based forests can conserve the forest ecosystem by applying waqf principles. This initiative has been implemented in several places in Indonesia. The limited funds available for waqf-based forest development require nazhir to carefully choose the best location so that the asset can function optimally. However, no specific research has been conducted to guide the selection of the best location for this purpose. This study aimed to identify potential criteria to help determine the best site for developing a waqf-based forest. Several methods were used to collect the necessary data, including literature reviews, in-depth interviews, field observations, and focus group discussions. This study identifies four crucial criteria when selecting the best locations: a) legal, b) physical and biophysical, c) high conservation value and benefits, and d) management. In addition, each criterion has sub-criteria. Among all, legal issues receive the highest highlight as unresolved regulations can affect a forest's ownership and function. This study was the first to discuss these criteria. Future research should quantify the criteria suggested using GIS and conduct more field observations in existing waqf-based forests in Indonesia.